2014
DOI: 10.1007/s11269-014-0519-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Streamflow Response to Climate Change and Human Activities in the Wei River Basin, China

Abstract: This final master work presents the results of the evaluation of the model Dynamic Water Balance (DWB) model at daily scale to simulate runoff in tropical watersheds. The present project used as input dataset information generated in the framework of the 2018 National Water Study developed by IDEAM. Therefore, 30 out of 497 watersheds area selected to be assessed in this study. The selection of the watersheds is made through the unsupervised k-means classification algorithm that considered morphometric, hydroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 74 publications
6
61
1
Order By: Relevance
“…Nonetheless, the above results indicate that LULC changes contributed considerably to decreased runoff, as reported in previous studies (e.g., Zhang et al, 2011;Zuo et al, 2014;. Additionally, the results suggest that vegetation restoration due to the GGP reduced surface runoff, which agrees with the results of other studies (e.g., Li et al, 2009;Nunes et al, 2011).…”
Section: Isolated Impacts Of Lulc Changesupporting
confidence: 91%
See 2 more Smart Citations
“…Nonetheless, the above results indicate that LULC changes contributed considerably to decreased runoff, as reported in previous studies (e.g., Zhang et al, 2011;Zuo et al, 2014;. Additionally, the results suggest that vegetation restoration due to the GGP reduced surface runoff, which agrees with the results of other studies (e.g., Li et al, 2009;Nunes et al, 2011).…”
Section: Isolated Impacts Of Lulc Changesupporting
confidence: 91%
“…Another study based on the relationship between precipitation and runoff from 1966 to 1970 showed that runoff mainly decreased due to precipitation before the 2000s and due to human activity thereafter, which became dominant (with a contribution of greater than 76 %) (Zhang et al, 2011). The different results reported by Zuo et al (2014) and Liang et al (2015) suggest that assessing the impacts of LULC and climate changes on runoff in relatively large basins (over 1000 km 2 ) is difficult (Chawla and Mujumdar, 2015;Peng et al, 2015b) due to their complex effects on streamflow (Fu et al, 2007) and the variable boundary conditions (Chen et al, 2011;Niraula et al, 2015).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In the climate elasticity method, the parameter n in the Yang equation was estimated according to Equations (12) and (19), based on mean P, E 0 , and R in the baseline period; the obtained n value is 1.562. Using Equations (20) and (21), the elasticity coefficients of runoff to P (ε P ) and E 0 (ε E0 ) were calculated as 1.994 and −0.994, respectively.…”
Section: Climte Elasticity Analysismentioning
confidence: 99%
“…Mengistu and Sorteberg (2012) applied the SWAT model to test the sensitivity of annual streamflow to climate change within the Eastern Nile River basin and results indicated that the dependence of the response on the strength of the changes was not linear. By using sensitivity-based method and dynamic water balance model, Zuo et al (2014) identified streamflow response to climate change in the Wei River Basin.…”
Section: Introductionmentioning
confidence: 99%